Who "owns" the cloud? An empirical study of cloud governance in cloud computing in Ghana - Joseph Kofi Wireko; Kenneth Kwame Azumah (International Telecommunications Society (ITS), 2017)
Cloud Computing is being widely adopted globally due to its economies of scale, convenience and operational agility to organizations. With Cloud computing, organizations, institutions and companies no longer need to invest heavily in such resources, but instead have the option to migrate to a Cloud model enabling them to purchase or lease resources on line. In an economic context where companies are seeking to make the most from their investments and minimize operating costs, Cloud computing is seen as the solution for competitiveness. The benefits of Cloud computing are therefore of immense importance to the developmental needs of sub-Saharan African countries especially under the Information Communication and Technology for Development (ICT4D) program and the Smart Cities agenda. However, most developing countries, especially those in Sub-Saharan Africa stand the risk of not benefiting fully from the potential of Cloud computing service due to the absence of effective and well-structured decision making process of stakeholders and their accountabilities in Cloud implementation given that one of the basic principles of Cloud computing is that data may be posted or stored “anywhere in the world”. This research is an empirical based study that elicited concerns on Cloud services governance and regulation militating against the rapid adoption and use of Cloud computing in Ghana. Respondents were made up of ICT officers who were in the decision making roles regarding the adoption and implementation of Cloud computing in their respective organizations. The results showed that the diversity of technology, service offerings and lack of coherent legislations and governance hindered Cloud service implementation. This has led to many organizations in developing countries sticking to their data centres and private Clouds in a bid to remain “safe” and “own” their data rather than venture into the “unknown” Cloud where ownership and governorship policies are unclear.
Keywords: 330; Cloud governance; Cloud Computing; Data centres; Smart Cities